2019
DOI: 10.1111/jpy.12853
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic resolution of the genus Cyanothece (Chroococcales, Cyanobacteria), with a treatment on Gloeothece and three new genera, Crocosphaera, Rippkaea, and Zehria

Abstract: The systematics of single‐celled cyanobacteria represents a major challenge due to morphological convergence and application of various taxonomic concepts. The genus Cyanothece is one of the most problematic cases, as the name has been applied to oval‐shaped coccoid cyanobacteria lacking sheaths with little regard to their phylogenetic position and details of morphology and ultrastructure. Hereby we analyze an extensive set of complementary genetic and phenotypic evidence to disentangle the relationships among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 119 publications
1
52
0
Order By: Relevance
“…Since that time, several authors have used the percent dissimilarity criterion to assist in defining species (Pietrasiak et al 2014;Bohunická et al 2015;Johansen et al 2017;Shalygin et al 2017;Vazquez-Martínez et al 2018;Mai et al 2018;Becerra-Absalón et al 2018;González-Resendiz et al 2018a, 2018bMareš et al 2019;Pietrasiak et al 2019). These authors all found a clear discontinuity between interspecies dissimilarity and intraspecies dissimilarity consistent with both Erwin & Thacker (2008) and Osorio-Santos et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, several authors have used the percent dissimilarity criterion to assist in defining species (Pietrasiak et al 2014;Bohunická et al 2015;Johansen et al 2017;Shalygin et al 2017;Vazquez-Martínez et al 2018;Mai et al 2018;Becerra-Absalón et al 2018;González-Resendiz et al 2018a, 2018bMareš et al 2019;Pietrasiak et al 2019). These authors all found a clear discontinuity between interspecies dissimilarity and intraspecies dissimilarity consistent with both Erwin & Thacker (2008) and Osorio-Santos et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in secondary structure of conserved domains of the 16S-23S ITS region can be used as autapomorphies, but differences should be supported by other evidence, such as minor morphological differences, major ecological differences, or demonstrated differences in other genes. The most recent pragmatic criterion that has not yet failed to clearly separate species when intraspecies variation is known is the percent dissimilarity of aligned ITS regions in orthologous ribosomal operons (Erwin and Thacker 2008, Osorio-Santos et al 2014, Bohunick a et al 2015, Shalygin et al 2017, V azquez-Mart ınez et al 2018, Becerra-Absal on et al 2018, Gonz alez-Resendiz et al 2018b, Mai et al 2018, Mare s et al 2019. Phylogenetic analyses of aligned orthologous ITS regions can also be useful in demonstrating reciprocal monophyly within species (Perkerson et al 2011, V azquez-Mart ınez et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we selected a target gene from a cyanobacterium for further study, increasing the likelihood of selecting a genuine MCP. We chose the MCP homolog from the organism R. orientalis, a cyanobacterium belonging to the genus Rippkaea, a recently established phylogenetic lineage formerly assigned to the genus Cyanothece (Mareš et al, 2019). This putative MCP, referred to in the following as RoMCP, consists of 163 amino acids corresponding to a molecular weight of 17.1 kDa and shares 52.5% sequence identity with CrMCP.…”
Section: Identification Of a Bacterial Mcpmentioning
confidence: 99%